Innate Immunity Provides Biomarkers of Health for Teleosts Exposed to Nanoparticles - Torrealba, Débora; More-Bayona, Juan A.; Wakaruk, Jeremy; Barreda, Daniel R. (Frontiers in Immunology, 2019)
In recent years, the unique properties of nanoparticles have fostered novel applications in various fields such as biology, pharmaceuticals, agriculture and others. Unfortunately, this rapid integration into daily life has also led to environmental concerns due to uncontrolled release of nanoparticles into the aquatic environment. Despite increasing awareness of nanoparticle bioaccumulation in the aquatic environment, much remains to be learned about their impact on aquatic organisms and how to best monitor these effects. Herein, we provide the first review of innate immunity as an emerging tool to assess the health of fish health following nanoparticles exposure. Fish are widely used as sentinels for aquatic ecosystem pollution and innate immune parameters offer sensitive and reliable tools that can be harnessed for evaluation of contamination events. The most frequent bioindicators highlighted in current literature include, but are not limited to, parameters associated with cell recruitment of various leukocytes lineages, oxidative stress and cytokine production. Taken together, innate immunity bioindicators offer an alternative for improved assessment of the impact of nanoparticles on fish health.